Aporias of foreignness: transnational encounters in cinema. Issue 1 (2nd January 2018) - Marciniak, Katarzyna; Bennett, Bruce
ABSTRACT: This introduction examines the meaning of foreignness, drawing on Jacques Derrida's discussion of 'the aporia' to propose that foreignness is critically aporetic - undecidable and unstable. At a moment when racist political rhetoric is being normalized and xenophobic political movements are on the rise, thinking about 'aporias of foreignness' allows us to reflect upon questions of belonging and hospitality, and the complexity and historical contingency of the relationship between self and other, indigenous citizen and immigrant, asylum-seeker or refugee. The introductory chapter proposes that cinema is a crucial medium through which to rethink foreignness since cinema always involves a potentially disorienting encounter with the unfamiliar, an encounter that is at the centre of the work of artist Ai Weiwei in film and other media.